(untitled) (Research, Society and Development, 2020)
Staphylococcus aureus are microorganisms often associated with foodborne disease outbreaks, for the ability to produce and excrete thermostable enterotoxins. This work has as objective the research of Staphylococcus aureus in Nile Tilapia fish commercialized in the semi-arid region of Piauí. Were collected 50 tilapia samples from free markets, supermarkets and butchers, 25g of each tilapia sample was used for homogenization with 225 ml peptone saline for research Staphylococcus aureus 1 ml of each sample was placed in BHI broth (brain and heart infusion), after incubated at 37ºC for 24 hours, where those turbid tubes were seeded by depletion on mannitol agar plates. Suspected mannitol agar colonies were used for identification of Staphylococcus, Gram staining was subsequently performed, catalase proof and coagulase proof. After completion of the methodology described, S. aureus was found in 38 of 50 samples, making a total of 76% of positive samples for this microorganism. It was observed that most establishments that marketed the fish used for sampling did not have necessary hygiene (use of gloves by handlers, refrigerators and utensils to perform sanitized cutting) facilitating contamination. It is necessary, futher a more intense supervision by the responsible agencies, attention from handlers as well as consumers, aiming at reducing cases of contamination.